Nigerian Plantation Workers on Fernando Po in Nigerian Political Discourse and International Relations between 1939 and 1968 - Kruze, Piotr (Instytut Historii PAN, 2024)
The article deals with the stages of the development of the plantation economy in Spanish Guinea, especially on the island of Fernando Po, and the methods of bringing in the labour force for cocoa plantations. It describes the reasons for the immigration of Nigerians to Spanish Guinea, especially since the 1930s. The paper also presents the influence of foreign contract workers on official government relations between Madrid and Lagos.
p. 51-72
Summary in English and Polish
Keywords: Spanish Guinea; Nigeria; cocoa; plantations; labour force; African decolonisation; Francoist Spain